Analysis of laboratory findings in dogs with ehrlichiosis in Poços de Caldas, Minas Gerais - Neves, Jackeline; Barreto Elston, Lilian; Landim Brisola, Marcelo (Pubvet, 2021)
Ehrlichiosis is a disease of worldwide distribution and severe character, if undiagnosed and properly treated the prognosis is reserved. This article carried out data analysis from all adult canine male and female samples sent in a period from 2016 to 2019 to a commercial diagnostic laboratory located in Poços de Caldas city, Minas Gerais state, in Brazil. The samples were separated into a positive group (16), composed of dogs that presented Ehrlichia spp. morulae in blood smear and negative group (43), with healthy dogs. Descriptive statistics of hematological and biochemical parameters of each group were previously performed and the comparison analysis was tested with F Test and Kruskal-Wallis Test, with a significance level of 5%. The significant parameters in this study were: VCM (P = 0.02), CHCM (P = 0.0005), Leu/mm³ (P = 0.002), Lin% (P = 0.005), Plat x 10³/mm³ (P < 0.0001), PPT (P = 0.02) e ALT (P = 0.009). The laboratory findings were similar to those was described in the literature. However, they are non-specific, being required for diagnostic the association with clinical history, physical examination and other complementary tests.